If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -2(x + -4) = 4x Reorder the terms: -2(-4 + x) = 4x (-4 * -2 + x * -2) = 4x (8 + -2x) = 4x Solving 8 + -2x = 4x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-4x' to each side of the equation. 8 + -2x + -4x = 4x + -4x Combine like terms: -2x + -4x = -6x 8 + -6x = 4x + -4x Combine like terms: 4x + -4x = 0 8 + -6x = 0 Add '-8' to each side of the equation. 8 + -8 + -6x = 0 + -8 Combine like terms: 8 + -8 = 0 0 + -6x = 0 + -8 -6x = 0 + -8 Combine like terms: 0 + -8 = -8 -6x = -8 Divide each side by '-6'. x = 1.333333333 Simplifying x = 1.333333333
| -7(4-m)=5m | | y=0.05x^2-39 | | x^2+12x+50=15 | | x^2+2x-4=2x^2+5 | | 3(x+1)-5(x+2)= | | 20x^2+3x-3=0 | | 6y-3(y+6)=0 | | (3x+3)-(5x+10)= | | x^2+17x+78=0 | | 1x(x)=400 | | 2.4+3.9x=77.3 | | 5-3x(-3)=14 | | 0.56+0.42t=1.34t-0.82 | | 3.5x-4.5=23.5 | | -21=7+4u | | X-17(-3)=14 | | 4(x+2)=8(6-2x)+20x | | n=(500-2Q)Q-20Q | | -5(y+10)= | | 8.8x+28.08=-11.2x+27.06 | | 8.8x+28.08=-11.2x+27 | | 2x+(x-30)+x=180 | | 5x^2+6y^2-10z^2+30=0 | | 72+3m+2(4-m)= | | 7.3x-2.8=19.1 | | 2=3(x-3)-(x-5) | | 2(6x-1)-5(x+6)=5(x+1) | | 7x+15-3x=12+(7*2+4*4)*2 | | 7+7(x-1)=4-4(x-5) | | 2(3-m)-3(4+m)= | | (x+3)*(3x-5)=10 | | 16y-3=31-y |